1999
DOI: 10.1021/jp991725w
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Characteristics of Surface Diffusion in Reversed-Phase Liquid Chromatography

Abstract: The thermodynamic properties of surface diffusion in reversed-phase liquid chromatography (RPLC) were analyzed in connection with the thermodynamics of surface diffusion in gas chromatography systems and of phase equilibrium in RPLC. The results suggest that the activation energy of surface diffusion in RPLC consists of only two contributions, corresponding to a hole-making and a bond-breaking process. The former is close to the activation energy of the mobile phase viscosity; the latter is correlated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 45 publications
(93 citation statements)
references
References 41 publications
5
87
1
Order By: Relevance
“…On the basis of these results, we proposed a surface-restricted molecular diffusion model for surface diffusion as a first approximation of the mechanism of surface diffusion and tried to consistently explain some intrinsic characteristics of surface diffusion. [24][25][26][27][28][29][30] The semi-logarithmic plots between the ratios DLs/Dm and Ds/Dm and -Qst in Fig. 6 fluctuate around a single straight line, although there is some scatter.…”
Section: Mechanism Of Surface Diffusionmentioning
confidence: 90%
“…On the basis of these results, we proposed a surface-restricted molecular diffusion model for surface diffusion as a first approximation of the mechanism of surface diffusion and tried to consistently explain some intrinsic characteristics of surface diffusion. [24][25][26][27][28][29][30] The semi-logarithmic plots between the ratios DLs/Dm and Ds/Dm and -Qst in Fig. 6 fluctuate around a single straight line, although there is some scatter.…”
Section: Mechanism Of Surface Diffusionmentioning
confidence: 90%
“…Physical meaning of the activation energy of surface diffusion Figure 8 shows the correlation between E s and Q st for two homologous series [48]. For both series, E s increases almost linearly with increasing -Q st but is not equal to zero at Q st = 0.…”
Section: 33mentioning
confidence: 99%
“…This result suggests that there may be a kind of intimate correlation between surface diffusion and molecular diffusion [24]. From these observations, K. M. and Guiochon have proposed a surface-restricted molecular diffusion model as a first approximation for the mechanism of surface diffusion [16,[23][24][25][28][29][30][31] and formulated the new model on the basis of the absolute rate theory [32]. On the other hand, in In Fig.…”
Section: Dependence Of C S D S On Retention Strengthmentioning
confidence: 99%
“…Additionally, K. M. and Guiochon [16,17,23,26,[29][30][31][33][34][35][36][37] have shown that an EEC is also established for surface diffusion in RPLC under various conditions of sample compounds and stationary and mobile phases. They analyzed some thermodynamic data concerning the retention equilibrium and surface diffusion in more detail on the basis of the four approaches proposed by Krug et al [38][39][40] and strictly demonstrated the establishment of the extra-thermodynamic relationship, i. e., EEC, for both the retention equilibrium and surface diffusion in RPLC [30,31,33,34,37,41].…”
Section: Extra-thermodynamic Properties Of D Lsmentioning
confidence: 99%